EFL learners' metacognitive awareness in listening strategies: A study in Indonesian higher education - Theodesia Lady Pratiwi; Leil Badrah Zaki; Elsha Ridzky Fadila Darsono (University of Muhammadiyah Malang, 2025)
The goal of this research is to investigate metacognitive awareness in listening strategies among English Language Education students. To achieve its goal, this research employed a mixed-methods approach, combining a questionnaire and interviews. The original questionnaire used in this research is Vandergrift's Metacognitive Awareness Listening Strategy (MALQ). Participants were 68 students of the English Language Education Department. The data analysis in this study describes the listening strategies used by English Language Education Department students. The data analysis of this study showed the listening strategies used by EFL students in the English Language Education Department. The findings showed that the problem strategy was the most widely used strategy by the students, shown by the highest mean score of 4.93/6.00. It was followed by other strategies, namely: planning & evaluation, direct attention, mental translation, and person knowledge strategies. Thus, the person knowledge strategy is the least used by the students. Therefore, in other words, students prefer using their prior knowledge and contexts to understand when they are listening to translate words in their head, maintain concentration, compare the effects of listening, and judge the difficulty level of listening.